2015
DOI: 10.3758/s13414-015-1028-9
|View full text |Cite
|
Sign up to set email alerts
|

Spatial negative priming: In touch, it’s all about location

Abstract: Spatial negative priming (SNP) refers to the finding that responses to stimuli that are presented from previously ignored locations are slowed relative to responses to stimuli presented from previously unstimulated locations. To date, this effect has been demonstrated in vision, audition, and touch. Importantly, however, the cognitive processes involved differ between vision and audition. Although SNP is attributable to feature mismatch in the auditory modality, it is primarily caused by response inhibition in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…That is, if RT is slower to a probe target at the prime distractor location than to a probe at a new location requiring the same response (and otherwise equated on relation to the prime trial), then there is clearly a location-specific effect. This exact effect was found by Wesslein, Spence, Mast, and Frings (2016) in an investigation of SNP in the tactile domain. In their experiment, subjects responded to one of two possible vibrotactile stimuli applied to the left or right wrist, forearm or upper arm.…”
mentioning
confidence: 64%
See 3 more Smart Citations
“…That is, if RT is slower to a probe target at the prime distractor location than to a probe at a new location requiring the same response (and otherwise equated on relation to the prime trial), then there is clearly a location-specific effect. This exact effect was found by Wesslein, Spence, Mast, and Frings (2016) in an investigation of SNP in the tactile domain. In their experiment, subjects responded to one of two possible vibrotactile stimuli applied to the left or right wrist, forearm or upper arm.…”
mentioning
confidence: 64%
“…Insofar as the present experiment actually shows a benefit (in error rates) to a response associated with a distractor, the answer here appears to be Bno.L ocation-specific SNP has implications for recent discussions of differences between sensory modalities. As mentioned earlier, Wesslein et al (2016) demonstrated a location-specific effect in touch. Because previous research (Buckolz et al, 2004;Buckolz, Edgar et al, 2012;Guy et al, 2006) seemed to indicate that SNP in the visual modality is due to response inhibition, Wesslein et al naturally concluded that the mechanism underlying SNP differs between touch and vision.…”
mentioning
confidence: 83%
See 2 more Smart Citations
“…That is, when a distractor stimulus of one trial (the prime) is repeated as target stimulus on the subsequent trial (the probe)-which is the case in the so-called ignored repetition condition of the negative priming (NP) paradigm, then probe performance is slower and/or more error prone, compared with a control condition without stimulus repetitions. Such NP effects have been documented for tactile stimuli (Frings, Amendt, & Spence, 2011;Frings, Bader, & Spence, 2008;Wesslein, Spence, Mast, & Frings, 2016), for stimuli of other sensory modalities (e.g., visual : Tipper, 1985;auditory: Mayr & Buchner, 2007;olfactory: Olsson, 1999), as well as across different stimulus modalities (audiovisually: Buchner, Zabal, & Mayr, 2003).…”
mentioning
confidence: 95%